2018
DOI: 10.1111/his.13654
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic pathological factors in radical cystectomy after neoadjuvant chemotherapy

Abstract: We confirm that the traditional and routinely reported histological parameters in RC post-NAC remain the most powerful prognosticators of disease course. The significance of TRG in the bladder remains unconfirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
8
1
Order By: Relevance
“…Moreover, we considered the relationship between NAC and LVI. Although there was no report that evaluated LVI before and after total resection as in this study, some reports discussed that the presence or absence of LVI after NAC became a prognostic factor in bladder cancer and other cancers [33][34][35]. In this study, there was no significant difference in the disappearance of LVI at RC according to the use of NAC in the LVI+ group at first TURBT (p = 0.282).…”
Section: Discussioncontrasting
confidence: 51%
“…Moreover, we considered the relationship between NAC and LVI. Although there was no report that evaluated LVI before and after total resection as in this study, some reports discussed that the presence or absence of LVI after NAC became a prognostic factor in bladder cancer and other cancers [33][34][35]. In this study, there was no significant difference in the disappearance of LVI at RC according to the use of NAC in the LVI+ group at first TURBT (p = 0.282).…”
Section: Discussioncontrasting
confidence: 51%
“…Our findings may be in contrast to another study investigating the prognostic value of TRG in muscle-invasive bladder cancer. 16 This multicenter study by Brimo and colleagues also identified TRGs as a prognostic parameter in univariable analyses, but this was not confirmed in multivariable analysis. However, there are some important differences between the study of Brimo and colleagues and our study.…”
Section: Discussionmentioning
confidence: 89%
“…First, our sample size met the requirement of the power calculation, while the study of Brimo and colleagues may have been underpowered (n = 165). Moreover, we excluded aggressive histomorphologic variants, in line with the large randomized controlled trials on neoadjuvant chemotherapy in muscle-invasive bladder cancer, 17,18 whereas Brimo et al 16 did not. 16 Taken together, our study provided a multicenter validation of the prognostic significance of TRG in muscleinvasive bladder cancer after neoadjuvant chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Sir : We read with interest the report by Brimo questioning the relevance of tumour regression grade (TRG) after neoadjuvant chemotherapy (NAC) and cystectomy in patients with muscle‐invasive bladder cancer …”
mentioning
confidence: 99%
“…Sir: We read with interest the report by Brimo questioning the relevance of tumour regression grade (TRG) after neoadjuvant chemotherapy (NAC) and cystectomy in patients with muscle-invasive bladder cancer. 1 Whereas classic prognosticators such as T stage, N stage and margin status have been shown to be independent predictors of survival, this is not the case for TRG of the primary tumour (TRG PT ). However, the informative nature of TRG PT may be impacted on by the influence of transurethral resection in the primary tumour (PT).…”
mentioning
confidence: 99%